Thriving in the challenge of geographical dislocation: A case study of elite Australian footballers - Harris, M.; Myhill, M.; Walker, J. (International Journal of Sports Science, 2012)
Young adult athletes are often required to relocate as part of their career progression. The transition between their 'old' and 'new' lives can have a positive or negative effect on their future career. The purpose of this study was to identify the processes and characteristics of thriving in periods of geographical dislocation; particularly the move away from the `familiar` to the `unfamiliar`. A partially mixed, sequential design was employed, initially to identify the individualities of a group of 24 elite athletes. Despite their homogeneity on a range of instruments, the outcome variations were not adequately explained. Subsequently, the particular characteristics and processes that contribute to thriving were examined through a sequence of semi-structured interviews, and analysis. The responses that led to positive outcomes (thriving), in comparison to less positive (surviving), or even negative (languishing) outcomes are identified and discussed. The findings inform the need for a more nuanced and detailed cyclic, rather than linear, approach to the transition and any associated intervention strategies. Further research is needed to examine this new approach to managing transitions with different groups of participants and in other dislocating and transitional contexts.